2017
DOI: 10.1105/tpc.16.00822
|View full text |Cite
|
Sign up to set email alerts
|

CALCIUM-DEPENDENT PROTEIN KINASE5 Associates with the Truncated NLR Protein TIR-NBS2 to Contribute to exo70B1-Mediated Immunity

Abstract: Calcium-dependent protein kinases (CPKs) function as calcium sensors and play important roles in plant immunity. Loss of function of the exocyst complex subunit EXO70B1 leads to autoimmunity caused by activation of TN2, a truncated Toll/interleukin-1 receptor-nucleotide binding sequence protein. Here we show, based on a screen for suppressors of , that-activated autoimmune responses require However, the CPK5 homologs CPK4, CPK6, and CPK11, which were previously reported to function redundantly with CPK5 in eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 54 publications
(92 reference statements)
5
97
0
3
Order By: Relevance
“…Recent reports showed that the repression of auxin pathway improved the resistance to bacterial pathogen (French et al, 2018;Navarro, 2016). The gene Araip.CMC8E might code for calcium-dependent protein kinase, which could perceive changes in intracellular calcium concentrations to transmit defence signal in response to PAMPs and pathogen effectors (Liu et al, 2017;Wang et al, 2018a). The gene Araip.CZ54N was predicted to encode for serine/threonineprotein phosphatase, which was reported to be involved in hypersensitive response (Zhou et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports showed that the repression of auxin pathway improved the resistance to bacterial pathogen (French et al, 2018;Navarro, 2016). The gene Araip.CMC8E might code for calcium-dependent protein kinase, which could perceive changes in intracellular calcium concentrations to transmit defence signal in response to PAMPs and pathogen effectors (Liu et al, 2017;Wang et al, 2018a). The gene Araip.CZ54N was predicted to encode for serine/threonineprotein phosphatase, which was reported to be involved in hypersensitive response (Zhou et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…To maintain membrane association, proteins undergo reversible palmitoylation on a close cysteine or harbor a basic domain in the VNTD (Chehab et al ., ) which can be counteracted by phosphorylation. The reversibility of this process allows proteins to shuttle between cytoplasm and membranes, as observed for AtCPK10/30/32 that translocate to the nucleus in response to nitrate (Liu et al ., 2017a). Palmitoylation has also been observed in vitro for AtCPK16 (Stael et al ., ) and in vivo for AtCRK2 and nine CPKs (Hemsley et al ., ).…”
Section: Structure and Regulation Of Cdpks/crksmentioning
confidence: 99%
“…In stable transgenic A. thaliana plants expressing CPK5-YFP the co-expression of ABI1-1mcherry results in a stronger effect than ABI1-11-mcherry ( Fig. S5A) and leads to tiny plants and lethality for the ABI1-1 variant, reminiscent to a constitutive 'enhanced SAR' phenotype (9) and auto-immunity (10). This finding suggests an over-induced immune response caused by already activated CPK5-signaling plus an additional synergistic factor through phosphatase ABI1-1.…”
Section: Discussionmentioning
confidence: 99%